Chlamydomonas protein kinase MAK phosphorylates FAP256/CEP104 and regulates axonemal microtubule assembly - Yi Zhang; Xinjia Yang; Junmin Pan (Proceedings of the National Academy of Sciences, 2025)
The formation of cilia involves the assembly of axonemal microtubules, the structural core of the organelle, from tubulins that are delivered by intraflagellar transport and diffusion. Whether and how this process is controlled are not clear. Here, we show that Chlamydomonas MAK (CrMAK), related to mammalian ICK/MAK, regulates axonemal microtubule assembly by phosphorylating FAP256/CEP104, a microtubule plus-end tracking protein. CrMAK, primarily present in cilia, associates with the axoneme via its C-terminal tail, and is enriched at the ciliary tip during active ciliary assembly. It is constitutively active during this process and acts downstream of a ciliary length-regulatory complex composed of LF1, LF3, and LF2, a CCRK homologue. Loss of CrMAK or its kinase activity leads to aciliated cells. CrMAK interacts with and phosphorylates FAP256/CEP104 and dephosphorylation of FAP256/CEP104 impairs ciliary assembly. These findings reveal a molecular mechanism governing the assembly of axonemal microtubules.